Two cases of late-onset Argininosuccinic aciduria with normal results at newborn screening - Marcão, Ana (2015)
Argininosuccinic aciduria (ASA) is an autosomal recessive metabolic disorder caused by Argininosuccinate Lyase (ASL) deficiency, and it is the second most frequent urea cycle disorder, with an estimated frequency of 1:70 000. The human ASL gene is located on chromosome 7q11.21 and comprises 16 exons encoding a 464 amino acids long monomer. The enzyme is functional in a homotetrameric structure and is mainly expressed in the liver, although it can be found in several other tissues. The clinical presentation of ASA is very heterogeneous, ranging from asymptomatic to severe hyperammonemic neonatal-onset cases. Complex clinical phenotypes, with neurological deficits and hepatic complications adding to hyperammonemic episodes, are often observed. Biochemically, ASA is usually characterized by elevation of both citrulline and argininosuccinic acid in plasma and urine, but also at this level heterogeneity is observed, adding to a poor correlation found between residual enzymatic activity and the severity of the clinical phenotype. Newborn Screening (NBS) for ASA is widely established although some paradoxal results can be obtained due to the clinical and biochemical ASA heterogeneity: asymptomatic cases can be detected and, on the contrary, late-onset forms with important clinical manifestations observed since the first months of live can be missed due to normal biochemical results. ASA was included in the Portuguese NBS Program in 2005, based on elevated argininosuccinic acid blood levels. During these ten years of NBS two cases were identified and two other were missed. The missed cases were two brothers with a late-onset clinical form, which presented completely normal results at NBS. They are homozygous for R12Q mutation, which is a mutation reported to be associated with a mild clinical form of the disease and frequently found in late-onset ASA cases. Based on this finding it is important to keep in mind that a late-onset form of ASA should be considered for a child with clinical signs fitting this disease, even if NBS had a normal result.